A Descriptive Study on Energy Intake, Nutrition Knowledge, and Nutritional Status Among Adolescents at SMKN 1 Kademangan, Blitar Regency - Nadya Chantika Rahayu; Nur Hatijah; Annas Buanasita; Nurul Hindaryani (Journal of Nutrition Explorations, 2025)
Adolescents are vulnerable to nutritional problems due to imbalanced energy intake and limited nutritional knowledge, which can affect their nutritional status. This descriptive quantitative study aimed to assess energy intake, nutrition knowledge, and nutritional status among adolescents at SMKN 1 Kademangan, Blitar Regency. A total of 71 students were selected through proportional random sampling. Data were collected using validated questionnaires, two 24-hour dietary recalls, and anthropometric measurements. Energy intake was analyzed using NutriSurvey and NutriCal, and nutritional status was determined using BMI-for-age (BMI/A) based on WHO standards. The results showed that 91.5% of respondents had normal nutritional status, 7.0% were overweight, and 1.4% were obese. In terms of nutrition knowledge, 62% had good knowledge, 35.2% moderate, and 2.8% poor. Meanwhile, 85.8% of respondents experienced varying levels of energy intake deficits (40.8% severe, 22.5% moderate, 22.5% mild), and only 14.1% had normal energy intake. Despite the high prevalence of energy deficits, most respondents maintained a normal BMI-for-age. This suggests that other factors may influence nutritional outcomes. Strengthening nutrition education and promoting healthy eating behaviors are recommended to support adolescent health.